The big end of town : big business and corporate leadership in twentieth-century Australia - Fleming, Grant A., 1964- (Cambridge University Press, 2004)
Never before has a book been published which provides such a comprehensive study of Australian corporate leadership over the past 100 years. Written by a team of economic historians The Big End of Town is the first proper business history of twentieth-century Australia. This book traces the evolution of large business enterprises in Australia, from the giants of the nineteenth century - such as Dalgety's, CSR and BHP - to the contemporary leaders in Newscorp and Qantas. It delves into why the market leaders became the major players, examines what was crucial to their success, and their roles in leading the Australian economy. By investigating their evolution this book provides a useful evaluation of the factors that have led to their competitive success and provides an essential guide for all businesses in Australia and beyond.